2009
DOI: 10.1002/bin.297
|View full text |Cite
|
Sign up to set email alerts
|

A replication of the RIRD strategy to decrease vocal stereotypy in a student with autism

Abstract: This study was conducted to decrease vocal stereotypy in a student with autism. Results of functional analysis indicated that vocal stereotypy was maintained by automatic reinforcement. We used the Response Interruption and Redirection (RIRD; Ahearn, Clark, & McDonald, 2007) strategy to decrease the vocal behavior. An ABAB design was used. Results indicated that the RIRD intervention successfully reduced the target behavior. Results are discussed and implications for practice are provided. Copyright © 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 29 publications
7
39
2
2
Order By: Relevance
“…However, it is noted that there were no data on long term follow-up reported in the Schumacher and Rapp study. Future research could look at implementing RIRD in more naturalistic settings (see Liu-Gitz & Banda, 2010) to increase generality of the results.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is noted that there were no data on long term follow-up reported in the Schumacher and Rapp study. Future research could look at implementing RIRD in more naturalistic settings (see Liu-Gitz & Banda, 2010) to increase generality of the results.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 15 studies identified in Lydon et al (2013) and Wong et al (2014) that demonstrated a reduction in vocal stereotypy, 5 of those studies were included in both reviews (Ahearn et al, 2007;Ahrens et al, 2011;Cassella, Sidener, Sidener, & Progar, 2011;Liu-Gitz & Banda, 2010;Miguel, Clark, Tereshko, & Ahearn, 2009). Participants ranged in age from 3 years to 11 years old.…”
Section: Response Interruption and Redirection Interventionsmentioning
confidence: 99%
“…Vocal stereotypy, in particular, may significantly interfere with social inclusion (Lanovaz & Sladeczek, 2012). These repetitive behaviors, a prominent characteristic of ASD, also interfere with and reduce a student's time spent on learning and social interactions (Liu-Gitz & Banda, 2010). In addition, children with ASD tend to display these repetitive behaviors throughout adolescence and adulthood and they can greatly impact their post-high school opportunities (Schall & McDonough, 2010).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Again, behavioral intervention research can be subdivided into two overarching categories—consequence-based and antecedent-based interventions. Some of the consequence-based intervention strategies that have been used to treat stereotypies (e.g., repetitive vocalizations) and/or SIB in ASD and other developmental disabilities, include physically or verbally (e.g., saying, “no”) blocking the individual from engaging in the behavior (i.e., response interruption and redirection/response blocking) (Ahearn et al 2007; Koegel et al 1974; Liu-Gitz and Banda 2010), removal of a positive consequence when the stereotypic behavior occurs (i.e., response cost procedures) (Athens et al 2008; Sidener et al 2005), reinforcing other behaviors the individual displays instead of the problematic behavior (i.e., differential reinforcement) (Azrin et al 1988) and functional communication training (FCT; Kennedy et al 2000). FCT is a multi-component intervention that involves teaching the individual an appropriate communication response that can be used to obtain the same reinforcer as the inappropriate behavior, while simultaneously withdrawing reinforcement of the inappropriate behavior (i.e., extinction) (Carr and Durand 1985).…”
Section: A Framework For Behavioral and Psychosocial Interventions Fomentioning
confidence: 99%